1997
DOI: 10.1007/s001200050117
|View full text |Cite
|
Sign up to set email alerts
|

Burch against Stamey. Comparison of two competing operative procedure

Abstract: Stress incontinence is the most frequent form of incontinence found in females. The usual method of surgery for this is to lift the bladder neck towards cranial and ventral. Two competitive techniques--bladder neck suspension in accordance with Stamey and colposuspension in accordance with Burch--were retrospectively investigated. A total of 95 women underwent surgery and it was possible to evaluate the postoperative course in 46 and 30 (total 76) patients respectively. Initially, both surgical techniques demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(36 reference statements)
0
1
0
1
Order By: Relevance
“…In contrast to the initial continence rate of >90% in studies with a follow‐up of <2 years [ 3, 8, 9, 20, 22], several subsequent investigations reported highly variable success rates of 30–80% after the Stamey procedure [ 5, 7, 12, 17, 19, 23, 27]. From these divergent results and the observation that incontinence recurred even >7 years after bladder neck suspension, it was suggested that the long‐term success rates reported for the procedure in several earlier studies might depend on the duration of the follow‐up, diverging criteria for the selection of patients and the experience of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the initial continence rate of >90% in studies with a follow‐up of <2 years [ 3, 8, 9, 20, 22], several subsequent investigations reported highly variable success rates of 30–80% after the Stamey procedure [ 5, 7, 12, 17, 19, 23, 27]. From these divergent results and the observation that incontinence recurred even >7 years after bladder neck suspension, it was suggested that the long‐term success rates reported for the procedure in several earlier studies might depend on the duration of the follow‐up, diverging criteria for the selection of patients and the experience of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Im Gegensatz zur initial berichteten postoperativen Kontinenzrate von > 90 % in solchen Serien, denen eine Nachbeobachtungszeit von < 2 Jahren zugrunde lag [2,10,11,29,32], wurden im Gefolge sehr unterschiedliche, zwischen 30 % und 80 % variierende Erfolgsraten beobachtet [5,6,9,13,14,23,26]. Unter Berücksichtigung dieser Ergebnisse und der Beobachtung der sich in Einzelfällen auch nach sehr langen Zeiträumen (> 7 Jahre) noch einstellenden Inkontinenzrezidive wurde vermutet, dass verschiedene Faktoren, wie bei-spielsweise die Länge der verschiedenen Studien zugrunde liegenden Nachbeobachtungszeit, die Patientenselektion und die Erfahrung der Operateure das Langzeitergebnis in entscheidendem Maûe zu beeinflussen vermögen.…”
Section: Patienten Und Methodikunclassified